In Vitro Efficacy Test on a Food Supplement for the Treatment of Urinary Tract Infections (UTIs) - Stasi, Simone; Mensa, Giulia; Motta, Paolo; Rapacioli, Silvia; Lupo, Silvia; Tiso, Domenico (Journal of Pharmacy and Nutrition Sciences, 2022)
Urinary tract infections (UTIs) are among the most common bacterial infections, representing a massive burden on healthcare systems and accounting for significant morbidity and healthcare expenditure. As bacteria generally cause UTIs, the primary therapy is defined by antibiotics, whose wide use can cause antibiotic resistance. In this scenario, using nutraceuticals to manage UTIs is an attractive alternative. This study aims to test the in vitro efficacy of a new food supplement for treating UTIs containing D-mannose, palmitoylethanolamide, HibCyn® (hibiscus extract), N-acetylcysteine and microencapsulated Lactobacillus rhamnosus LR04. The activity of the product was evaluated in terms of antimicrobial, antibiofilm, cytotoxic, antiinflammatory, and synergic activity with fosfomycin with respect to the main microorganisms responsible for UTIs, specifically Klebsiella pneumoniae, Enterococcus faecium, and Escherichia coli. “UTIVAL” food supplement has an action on both the inhibition and eradication of the biofilms formed by all the microorganisms. In the in vitro tests performed in this study, the activity of the product was effective at a concentration of 0.78 g/l. It was also possible to affirm that the product has an inhibiting effect on inflammation mediated by tumor necrosis factor αlfa (TNFα) in a concentration range of 0.04 to 0.625 mg/ml.